JAPANESE AND INDONESIAN EXPRESSIONS OF HOSPITALITY AT HOTEL - Savana, Azizia Freda; Lantang, Ayu Gardenia (Universitas Islam Sumatera Utara (UISU), 2023)
The research discusses Japanese and Indonesian expressions of hospitality at hotels. It is necessary to know how to use Japanese and Indonesian expressions in hospitality, how to welcome guests in time of check-in check out in Japanese and Indonesian. The students can better understand their use when working in Japanese hotels. In addition, this research can provide knowledge to the students when participating in Japanese language professional certification competencies. The method used in this research is the descriptive qualitative method and the research aims to find a systematic, factual, and accurate pictures of the use of expressions in Japanese and Indonesian in the scope of hospitality at hotels; for welcoming hotel guests: Asisatsu no hyogen and Yobikake no hyogen, for serving guests check-in; Aisatsu no Hyogen, Irai no Hyogen, and Gimon no Hyogen and Aisatsu no Hyogen, for serving guests check-out. There is a slight difference between the expressions used in Japanese and Indonesian. In Japanese, they use Hantei Youkyuu no Hyougen to welcome guests to a hotel, but in Indonesian such expressions are not used. In Indonesian, the expression Hantei Youkyuu no Hyougen when serving guests to check-in is not used in Indonesian version.